Evaluation of the Use of Privileged Funds of Yogyakarta on Cultural Sector in Sleman 2016 - Sulistiono, Bagus; Efendi, David (Forum Ilmu Sosial, 2018)
Since 2013, through Law No. 13 of 2012 on Specialties of Yogyakarta, Privileges Fund has handled 5 special privileges in Yogyakarta including a) the procedures for filling the positions, duties and authorities of the Governor and Vice Governor; b) local government Institution of DIY; c) culture; d) land; and e) spatial planning. In 2016, the Department of Culture and Tourism of Sleman Regency received a budget allocation of Rp. 3,629,781,050. This research using qualitative research in aims to describe and analyze the problems. Data collection techniques through interviews and documentation. Sources of data come from journals, research reports, official documents, and interviews to relevant sources. Data analysis techniques used are data reduction, data presentation, and conclusion. The findings: in 2016, the percentage of achievement realization of absorption and progress activities up to 100%. However, there are still some problems during the implementation of the Privileged Fund in 2016. These problems were the lack of socialization of government to the community on how to access Privileged Funds, a special relationship between the bureaucrats and the community in approval of the proposal, and the programs and activities that are considered not able to prosper the public in general. It concludes that still government has not been able to show the attitude of transparency, accountability and responsiveness to the community.